PENGARUH KEBIJAKAN KAS, LIQUIDITY, LEVERAGE DAN EARNING PER SHARE TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN MANUFACTUR LISTED DI BURSA EFEK INDONESIA - Suradi Suradi (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
This research aims is to analized the influence of Cash Ratio, Current Ratio, Debt to Total Aset (DTA), and Earning Per Share (EPS) to the Devidend police, which measure by Dividend Payout Ratio, to the manufacture company listed in Jakarta Stock Exchange, with the period of research is 2008 to 2011. The samples were collected panel data and it has resulting n = 40. The analysis model is using linier regression analysis to 10 go public corporation selected by purposive sampling method in Indonesian Stock Exchange with secondary data of Indonesian Capital Market Directory (ICMD). The research result partially found, that independent variable ( Cash Ratio, Current Ratio, Debt to Total Asset Ratio, and Earning per Share ) are influence to the Devident Payout Ratio, and according to Cash Ratio is significant domination influence to the Devident Payout Ratio. The research stimultant results is variable independent are influence to Divident Payout Ratio with significanty result of F 0,031 > 0,050. The adjusted R square (R2) value is 23,3 % mean while the others are 76,7 % influence by the other factors which is not included to the alalysis linier regression model. Key words : Deviden Payout Ratio, Cash ratio, Current Ratio, DTA, and EPS.